3D Immunocompetent Organ‐on‐a‐Chip Models. Issue 9 (17th June 2020) - Maharjan, Sushila; Cecen, Berivan; Zhang, Yu Shrike
Abstract: In recent years, engineering of various human tissues in microphysiologically relevant platforms, known as organs‐on‐chips (OOCs), are explored to establish in vitro tissue models that recapitulate the microenvironments found in native organs and tissues. However, most of these models have overlooked the important roles of immune cells in maintaining tissue homeostasis under physiological conditions and in modulating the tissue microenvironments during pathophysiology. Significantly, gradual progress is being made in the development of more sophisticated microphysiologically relevant human‐based OOC models that allow the studies of the key biophysiological aspects of specific tissues or organs, interactions between cells (parenchymal, vascular, and immune cells) and their extracellular matrix molecules, effects of native tissue architectures (geometry, dynamic flow, or mechanical forces) on tissue functions, as well as unravelling the mechanism underlying tissue‐specific diseases and drug testing. In this progress report, the different components of the immune system, as well as immune OOC platforms and immunocompetent OOC approaches that have simulated one or more components of the immune system, are discussed. The challenges to recreate a fully functional tissue system in vitro with a focus on the incorporation of the immune system are also outlined. Abstract : This progress report discusses the different components of the immune system, as well as immune organ‐on‐a‐chip (OOC) platforms and immunocompetent OOC approaches that have simulated one or more components of the immune system. The challenges to recreate fully functional tissue systems in vitro are also outlined with a focus on the incorporation of the immune system.